Sifat Fisik dan Organoleptik Yogurt Drink Susu Kambing dengan Penambahan Ekstrak Kulit Manggis (Garcinia mangostana L.) - Jeki Mediantari Wahyu Wibawanti; Rinawidiastuti Rinawidiastuti (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2018)
The objective of this studies were to determine the physical properties of viscosity and organoleptic of yogurt drink with the suplementation of mangosteen peel extract. The experimental design used was Completely Randomized Design (CRD) of the factorial pattern. The first factor was the difference of mangosteen peel extract level (0%, 3% and 6% v / v), while the second factor was the storage time of yogurt (0, 1, and 2 weeks) with 3 replications. The results showed that the supplementation of mangosteen peel extract on yogurt drink gave significant effect (p <0.05) on viscosity, color and sensory analysis (viscosity and texture). Yogurt drink was recommendation with mangosteen peel extract 3% (74.65cp), lightness (L) 79.89, redness (a*) 0.14 yellowness (b*) 2.32, sensory analysis of viscosity with score 2.84 (moderate viscosity), organoleptics of color 3.52 (white yelowness) and texture test with score 2.12 (moderate smooth). It can be concluded that the addition of mangosteen peel extract can improve the quality of physical, color, organoleptik yogurt drink. The use of mangosteen peel extract will increase the economic value and product diversification.